Respostas internacionais às crises de proteção de pessoas: a responsabilidade de proteger e o surgimento de um novo regime de proteção - Alex J. Bellamy (Revista Crítica de Ciências Sociais, 2014)
This essay examines contemporary debates about human protection by the UN Security Council and others in response to major humanitarian crises. It argues that there are clear signs of an emerging international human protection regime in the evolving practice of the Security Council and suggests that this regime is based on an accommodation between different moral accounts of humanitarian intervention. The first section examines some of the legal and moral debates that have arisen with respect to military intervention for protection purposes. The second section briefly reviews the Security Council’s practice and reveals an emerging new politics of protection. The third section argues that although the use of force and other coercive measures remains controversial, there is evidence to suggest that the Security Council is taking its protection responsibilities more seriously in a way consistent with the emergence of a new regime.